Multi-omics insights reveal the remodeling of gut mycobiome with P. gingivalis - Chen, Si; Niu, ChenGuang; Lv, WanQi (Frontiers in Cellular and Infection Microbiology, 2022)
As a keystone periodontal pathogen, Porphyromonas gingivalis (P. gingivalis) has suggested to be involved in the progression of systemic diseases by altering the intestinal microecology. However, studies concerning gut microbiome have focused entirely on the bacterial component, while the fungal community (gut mycobiome) has been overlooked. In this study, we aimed to characterize the alteration of gut mycobiome profile with P. gingivalis administration using mice fecal samples. Metagenomic analysis showed a distinct composition pattern of mycobiome and significant difference of beta diversity between control and P. gingivalis group. Some fungal species were differential characterized with P. gingivalis administration, among which Pyricularia pennisetigena and Alternaria alternata showed positive correlation with P. gingivalis. KEGG functional analyses revealed that three pathways, including “pentose and glucuronate interconversions”, “metabolic pathways” and “two-component" system” were statistically enriched with P. gingivalis administration. Moreover, the alteration of gut mycobiome was also closely related with serum metabolites, especially lipid and tryptophan metabolic pathways. Taken together, this study demonstrated the alteration of fungal composition and function with P. gingivalis administration for the first time, and investigated the fungi-bacterial interaction and fungi-metabolite interaction preliminarily, providing a whole insight of gut mycobiome remodeling with oral pathobiont through multi-omics analyses.